SISTEM PENDUKUNG KEPUTUSAN PENGHAPUSAN ASET MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING BERBASIS WEB PADA PT. ANDARU ARTI AGUNG - Tesa Lonika Siahaan (2021)
PT. Andaru Arti Agung is a company that dabbles in the export and import of fresh meat. The business processes at PT. Andaru Arti Agung include the tax management process, the company's resource planning process or often abbreviated as ERP and the aset management process. From some of these processes there are several difficulties in the aset management process, namely the process of submitting aset purchases, the process of calculating the value of asets, calculating the economic life of asets and the process of aset deletion, this is due to the lack of good aset management. The problem at PT. Andaru Arti Agung in the aset management process is how the asets owned can be known by type, quantity, economic age, aset value and how to calculate capital or capital asets. The method used is the straight line method to help manage asets, namely the depreciation process and the Simple additive weighting method for elimination. The results of this study are that PT. Andaru Arti Agung can have valid aset data, the exact amount can be known and the company's capital can be calculated from the form of asets.